1979
DOI: 10.1128/iai.24.2.371-378.1979
|View full text |Cite
|
Sign up to set email alerts
|

Immune and mitogenic responses by BALB/c, C3H/HeJ, and nude mice to Brucella abortus bacterin and lipopolysaccharide

Abstract: The immunogenic and mitogenic properties of Brucella abortus 1119-3 bacterin (BA) and biologically active B. abortus lipopolysaccharide (BA-LPS) were studied using normal and athymic (nude) BALB/c and C3H/HeJ mice. Although BA stimulated 2-mercaptoethanol-sensitive (2-ME-S) primary and secondary antibody responses in all mice, nude mice, in contrast to normal BALB/c and C3H/ HeJ mice, did not make substantial 2-mercaptoethanol-resistant (2-ME-R) antibody responses. Similarly, all mice injected with BA-LPS made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Experimental results in the present study also suggests that B. melitensis and B. abortus LPSs may exhibit similar biological actions. Interestingly, B. abortus LPS can activate spleen cells from LPS-resistant C3H/HeJ mice (28,32). However, it could not necessarily be reproduced by our preparation of B. melitensis LPS (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Experimental results in the present study also suggests that B. melitensis and B. abortus LPSs may exhibit similar biological actions. Interestingly, B. abortus LPS can activate spleen cells from LPS-resistant C3H/HeJ mice (28,32). However, it could not necessarily be reproduced by our preparation of B. melitensis LPS (data not shown).…”
Section: Discussionmentioning
confidence: 86%
“…Comparative investigations, both in vivo and in vitro, with endotoxin preparations from different organisms which have different properties should also prove useful. For example, Spellman and Reed (40) have reported that a crude preparation of B. abortius LPS induced "T-independent" primary IgM responses and "TD" secondary responses in both euthymic BALB/c and C3H/HeJ mice as determined by 2-mercaptoethanol sensitivity of the bacterial agglutinins. Athymic BALB/c mice also made secondary responses with some mercaptoethanol-stable agglutinin.…”
Section: Discussionmentioning
confidence: 99%
“…While C3H/HeJ cells are profoundly refractory to some highly purified LPS, however, the cells remain responsive to other endotoxins (e.g., Boivin) in which the endotoxin protein or lipid A-associated protein (35) is known to be bioactive. In addition, LPS from Brucella abortus (21,33), Pseudomonas aeruginosa (29), Porphyromonas (Bacteroides) gingivalis (5,7), and Bacteroides fragilis (12) are also known to activate C3H/HeJ cells. LPS isolated from rough (R-form) mutant members of the family Enterobacteriaceae had also been thought capable of stimulating C3H/HeJ cells, but Manthey and Vogel (19) clearly demonstrated that the effect disappeared when protein associated with the LPS was removed by repurification.…”
mentioning
confidence: 99%